Biopsychosocial Spiritual Conditions (BSC) of Street Buskers with Visual Disabilities in Bandung City - Juandi, Acep; Budiman, Rizky; Hastika, Nunung (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research on blind people is motivated by the fact that many buskers with blind people in the city of Bandung come from outside the city of Bandung, because according to them the city of Bandung is a city that is friendly to people with disabilities, especially the blind. This research aims to find out, understand and analyze the biological, psychological, social and spiritual conditions of street buskers with visual disabilities in the Diponogoro road area, Bandung City. This research used a descriptive qualitative approach, with purposive sampling using certain criteria, obtaining 5 main informants. and the five informants are street performers with visual disabilities in Bandung City. Data collection in this research was carried out by means of in-depth interviews and documentation studies. The research results show that basic biological needs are very lacking. Street buskers with visual impairments in the city of Bandung spend more time on the streets busking, so there is not enough other physical activity. Based on the results of research on psychological aspects, all informants felt happy when busking because they had no other work. On the social aspect, blind street buskers in the Jalan Diponegoro area, Bandung City, have good relationships with the environment or their friends. Furthermore, the spiritual aspect in this discussion is not discussed regarding the informant's religious observance, how often he prays, makes dhikr, or recite the Koran, but rather whether or not the informant has intentionally or unintentionally abandoned his religious obligations to busk.